Peran moderasi dukungan orang tua dalam hubungan antara ketidaksesuaian tujuan karier dan revisi tujuan karier dewasa muda: The moderating role of parental support in the relationship between career goal discrepancy and young adults' career goal revision. - Akmal, Sari Z (Persona:Jurnal Psikologi Indonesia, 2024)
This research aimed to examine the role of parental support, as an important construct in collectivist culture, in the relationships between career goal discrepancy and career goal revision among Indonesian young adults. We surveyed 357 first year private university students (Mage=18,70 years, SD=0,92; 67% female) who were hired by using the accidental sampling technique. We collected participants’ data by using The Negative Career Goal Discrepancies Scale (α=0,91), The Influence of Others on Academic and Career Decisions Scale (α = 0,85), and The Downward Goal Revision Scale (α=0,88). The moderation analysis showed that parental support was a statistically significant moderator of the relationship between negative career goal discrepancy and downward goal revision. The interaction effect between negative career goal discrepancies and parental support was significant in decreasing levels of career goals in young adults, both in the group who felt they had parents who were very supportive in achieving their career goals and those who were less supportive. It highlights the important role of parental support in career planning.